The concept of ma’ruf in the Qur'an and its implications for Islamic religious education - Alamsyah, Ganjar; Abdussalam, Aam; Rahmat, Munawar (Universitas Pendidikan Indonesia, 2022)
Abstract. This study examines the concept of Ma’ruf in the Qur’an and its implications for the formulation of Islamic Religious Education goals. This research is library research, using the thematic method (maudhu’i). From this research, it was found that the meaning of Ma’ruf indicates the meaning of everything that is considered good and is a virtue that is considered according to common sense and sharia.’ In the Qur’an, the term al-ma’ruf refers to the meaning of all forms of virtue in general, both vertical or spiritual-transcendental relationship with God and horizontal relationship with human, based on reason and syara’. Meanwhile, the implication of the meaning of Ma’ruf on the purpose of Islamic Religious Education is the creation of a world view as perfect human beings on the importance of building a civilization that can balance reason and syara’.